2002
DOI: 10.1023/a:1014093008857
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Despite the consensus regarding community integration as a major goal of mental health policy and the emergence of supportive independent housing as a critical component of community mental health services, mental health services research has not examined the extent to which housing and service characteristics are associated with community integration of persons with psychiatric disabilities in supportive independent housing. The main goal of this paper is to propose a conceptual model of factors influencing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(79 citation statements)
references
References 53 publications
2
74
1
2
Order By: Relevance
“…There have been no prior prevalence data based on the integrated community conceptual model proposed by Wong and Solomon (2002). We found that members of the Community Comparison Group were nearly twice as likely as those in the Schizophrenia Group to be in the top three categories in the Community Integration Scale (41 vs. 23%).…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…There have been no prior prevalence data based on the integrated community conceptual model proposed by Wong and Solomon (2002). We found that members of the Community Comparison Group were nearly twice as likely as those in the Schizophrenia Group to be in the top three categories in the Community Integration Scale (41 vs. 23%).…”
Section: Discussioncontrasting
confidence: 54%
“…We adapted the conceptual model of Wong and Solomon (2002) and its operationalization by Gulcur et al (2007). It consisted of 12 variables divided into 4 dimensions: Independence (goes places, shopping); Psychological integration (''moderate/very satisfied'' on neighborhood satisfaction, house/apt/residence satisfaction, emotional support from non-family, emotional support from family); Physical integration (joins in activities, does not avoid others, mean of agree/strongly agree on the Self-Esteem Scale (which served as an indicator of non-stigmatization); Social integration (number reliable non-kin C3, number of agency linkages C3, at least monthly attendance at church attendance or senior/recreational center, or consumer group program).…”
Section: Community Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Participation in diverse and meaningful activities provides opportunities for social connectedness (Sörgaard et al, 2001) and contributes to wellbeing and recovery (Lai et al, 2013;Windell & Norman, 2012). Wong and Solomon developed a model of community integration that is divided into four factors (i.e., psychological integration, physical integration, social integration, and independence; Gulcur, Tsemberis, Stefancic, & Greenwood, 2008;Wong & Solomon, 2002). This model provides a framework for the development of interventions that promote community integration.…”
Section: Introductionmentioning
confidence: 99%
“…Further research on the Wong and Solomon (2002) model identified specific variables relevant to each of the four domains. Specifically, psychological integration comprises quality of life, psychological well-being, and neighborhood cohesion; physical integration comprises organization participation and involvement in leisure activities; social integration represents social support and having individuals from one's neighborhood in his or her social network; and independence was closely associated with selfactualization (Gulcur et al, 2008).…”
Section: Introductionmentioning
confidence: 99%